Storia di un dottorato: storia medievale nell'Università di Firenze - Andrea, Zorzi (Scuole di dottorato, 2003)
The PhD course in Mediaeval History of the University of Florence is one of the oldest in the Italian university circuit. Founded in 1983 by Girolamo Arnaldi, Elio Conti and Raoul Manselli, all the cycles of the courses were launched, achieving results of the greatest significance in the sphere of research. Over the years, about sixty young students and a couple of dozen teachers have given shape to a human and intellectual experience based on exchange and the acceptance of different points of view. Traced out in this book is a brief history of the first twenty years, rendering account of the activities fostered and the research carried out, and providing the scientific and bibliographic profiles of each member.